2018
DOI: 10.1177/1536012117745386
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 in Nuclear Medicine for Imaging and Therapy

Abstract: Since its discovery, the human epidermal growth factor 2 (HER2) has been extensively studied. Presently, there are 2 standard diagnostic techniques to assess HER2 status in biopsies: immunohistochemistry and fluorescence in situ hybridization. While these techniques have played an important role in the treatment of patients with HER2-positive cancer, they both require invasive biopsies for analysis. Moreover, the expression of HER2 is heterogeneous in breast cancer and can change over the course of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 73 publications
(175 reference statements)
1
49
0
9
Order By: Relevance
“…Using 89 Zr-trastuzumab as a surrogate marker of targeted inhibition of effector molecules downstream of the HER2 signaling pathway has been conceptually proven, for example, with Hsp90 inhibition [ 24 ]. Currently, this imaging probe is investigated in the clinic not only for diagnostic and staging purposes but also as a marker of response to other targeted treatments (NCT01081600 for AUY922 HSP90 inhibitor, NCT01565200 for T-DM1) [ 25 ]. To the best of our knowledge, this is the first study that demonstrated the potential of 89 Zr-trastuzumab PET to monitor Src response to dasatinib treatment in trastuzumab-sensitive and trastuzumab-refractory breast cancer xenografts with proven Src activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using 89 Zr-trastuzumab as a surrogate marker of targeted inhibition of effector molecules downstream of the HER2 signaling pathway has been conceptually proven, for example, with Hsp90 inhibition [ 24 ]. Currently, this imaging probe is investigated in the clinic not only for diagnostic and staging purposes but also as a marker of response to other targeted treatments (NCT01081600 for AUY922 HSP90 inhibitor, NCT01565200 for T-DM1) [ 25 ]. To the best of our knowledge, this is the first study that demonstrated the potential of 89 Zr-trastuzumab PET to monitor Src response to dasatinib treatment in trastuzumab-sensitive and trastuzumab-refractory breast cancer xenografts with proven Src activity.…”
Section: Discussionmentioning
confidence: 99%
“…Biodistribution studies in humans based on imaging analysis may be required, because target expression in animal models may not reflect distribution in humans (39,40). Indeed, a recent study of positron emission tomography (PET) imaging with zirconium-89 labeled trastuzumab to assess HER2 status demonstrated substantial heterogeneity in HER2 expression in metastatic lesions within the same patients (41,42). Combining the imaging analysis with fludeoxyglucose F 18-labeled PET/computed tomography imaging enabled prediction of which patients would benefit from treatment with the HER2 ADC (41).…”
Section: Biodistribution Studiesmentioning
confidence: 99%
“…Molecular imaging using specific radiopharmaceuticals that target HER2 could offer a non-invasive option for better quantification and localization of HER2 overexpression and, thus, identify patients who may benefit from HER2-directed therapy. Several imaging tracers targeting HER2 have been reported, including radiolabeled mAbs, antibody fragments (Fab or F(ab) 2 ), nanobodies, or affibodies [6]. One of the most well studied radiotracers for HER2 imaging is 89 Zr-labeled trastuzumab, which allowed visualization and quantification of uptake in HER2-positive lesions for patients with metastatic BCa and other cancers in several clinical trials [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%